2016
DOI: 10.3847/0004-637x/832/1/80
|View full text |Cite
|
Sign up to set email alerts
|

On the White Dwarf Mass Problem of Cataclysmic Variables

Abstract: Recent observations show that the white dwarfs (WDs) in cataclysmic Variables (CVs) have an average mass significantly higher than isolated WDs and WDs in post-common envelope binaries (PCEBs), which are thought to the progenitors of CVs. This suggests that either the WDs have grown in mass during the PCEB/CV evolution or the binaries with low-mass WDs are unable to evolve to be CVs. In this paper, we calculate the evolution of accreting WD binaries with updated hydrogen accumulation efficiency and angular mom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Indeed, Nelemans et al (2016) found that an ejection similar to a common envelope might significantly affect the stability of mass transfer, particularly for systems with low-mass WDs. In another approach, Liu & Li (2016) calculated that if ∼ 20 − 30 per cent of the matter ejected during a nova eruption remains in the system forming a circumbinary disk, CVs with low-mass WDs would be more likely to become dynamically unstable.…”
Section: Origin Of Extra Angular Momentum Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Nelemans et al (2016) found that an ejection similar to a common envelope might significantly affect the stability of mass transfer, particularly for systems with low-mass WDs. In another approach, Liu & Li (2016) calculated that if ∼ 20 − 30 per cent of the matter ejected during a nova eruption remains in the system forming a circumbinary disk, CVs with low-mass WDs would be more likely to become dynamically unstable.…”
Section: Origin Of Extra Angular Momentum Lossmentioning
confidence: 99%
“…Mass growth of the WD during the CV phase or in a preceding short phase of thermal time-scale mass transfer for many CVs was investigated in detail in Wijnen et al (2015), concluding that both options can be ruled out as the main cause for the WD mass problem (see also Liu & Li, 2016). By plotting the predicted CV population in a mass ratio (q = M sec /M WD ) versus secondary mass (M sec ) diagram it became evident that mass growth was not the solution (Schreiber et al, 2016).…”
Section: The Wd Mass Problemmentioning
confidence: 99%
“…The detailed investigation of the process of accretion and the increase of mass in CVs, however, faces several difficulties like accretion leading to nova eruptions (thus decreasing the white dwarf mass) and the accumulated shells erupting and getting ejected. Detailed calculations show that thermaltimescale mass transfers are not effective in increasing the masses of white dwarfs in CVs (see, e.g., Liu & Li 2016). The discovery of a fast rotating and high magnetic field white dwarf in AR Sco opens up the possibility of episodic increase of mass in a CV and in the following we sketch a tentative scheme of repeated episodes of mass accretion as a reason for the high magnetic field and spin rate in AR Sco.…”
Section: Possible Evolution Of Ar Scomentioning
confidence: 86%
“…where η H and η He are the mass accumulation efficiencies for hydrogen and helium burning respectively, and −Ṁ 2 is the mass transfer rate. We refer to Hillman et al (2016) and Kato & Hachisu (2004) for the dependence of η H and η He on the WD mass and the mass transfer rate, respectively (see also Liu & Li 2016, for more details). The excess material is assumed to leave the binary at a rate of (|Ṁ 2 | −Ṁ WD ), taking away the specific AM of the WD.…”
Section: Modelmentioning
confidence: 99%